2018
DOI: 10.1016/j.celrep.2018.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Network Dynamics during Rearing Episodes

Abstract: SummaryAnimals build a model of their surroundings on the basis of information gathered during exploration. Rearing on the hindlimbs changes the vantage point of the animal, increasing the sampled area of the environment. This environmental knowledge is suggested to be integrated into a cognitive map stored by the hippocampus. Previous studies have found that damage to the hippocampus impairs rearing. Here, we characterize the operational state of the hippocampus during rearing episodes. We observe an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 55 publications
(81 reference statements)
2
65
1
Order By: Relevance
“…In contrast to mismatch novelty, uncharted novelty involves the exposure to a previously unvisited context and therefore it lacks a memory representation. Interestingly, a recent study using an uncharted novelty test showed increased theta-gamma CFC exclusively in EC pathways, but not in the CA3→CA1 pathway (Barth et al, 2018). Thus, in the absence of a memory representation, only EC-pathways conveying information about the environmental cues demonstrate enhanced theta-gamma coupling, lending support to our hypothesis.…”
Section: Behavioural Modulation Of Theta-gamma Cfc and Theta Synchronsupporting
confidence: 83%
See 3 more Smart Citations
“…In contrast to mismatch novelty, uncharted novelty involves the exposure to a previously unvisited context and therefore it lacks a memory representation. Interestingly, a recent study using an uncharted novelty test showed increased theta-gamma CFC exclusively in EC pathways, but not in the CA3→CA1 pathway (Barth et al, 2018). Thus, in the absence of a memory representation, only EC-pathways conveying information about the environmental cues demonstrate enhanced theta-gamma coupling, lending support to our hypothesis.…”
Section: Behavioural Modulation Of Theta-gamma Cfc and Theta Synchronsupporting
confidence: 83%
“…Importantly, increased CFC reached significance in the rearing-associated EC pathways (Barth et al, 2018). Overall, the changes found in mismatch novelty cannot be solely explained by the rearing behaviour.…”
Section: Behavioural Modulation Of Theta-gamma Cfc and Theta Synchronmentioning
confidence: 78%
See 2 more Smart Citations
“…In contrast to delta, the theta rhythm (6-10 Hz) in HC and connected structures is a wellorganized oscillation that is critical for spatial navigation and episodic memory (Winson, 1978, Buzsaki, 2002, Buzsaki & Moser, 2013; shows frequency and power correlations to locomotor speed (Whishaw & Vanderworf, 1973, McFarland et al, 1975, Maurer et al, 2005, Hinman et al, 2016 and behaviors related to active attention and environmental sampling (Aghajan et al, 2017, Barth et al, 2018; exhibits functionally-relevant cross-frequency coupling to gamma oscillations (>25 Hz) (Canolty et al, 2006, Tort et al, 2009, Shirvalkar et al, 2010; and coordinates robust spiking within the HC (Okeefe & Recce, 1993, Foster & Wilson, 2007, Johnson & Redish, 2007, and its projection targets (Sirota et al, 2008, that is critical for learning, decision making, and representations of ongoing, remembered, or imagined future experiences (Richard et al, 2013, Pfeiffer & Foster, 2013, Redish, 2016, Schacter et al, 2007.…”
Section: Introductionmentioning
confidence: 99%